E-029 Balloon-augmented target vessel sacrifice with liquid embolic agents. (4th July 2012) - Bhalla, T; Spiotta, A; Hui, F
Abstract : Introduction: Vessel sacrifice remains a valuable tool in the treatment of select vascular lesions. Conventionally, neurointerventionalists have relied on coil embolization as their primary means of vessel sacrifice since detachable balloons are no longer available. However, coil embolization can be expensive with long fluoroscopy times. We describe a novel technique for vessel sacrifice using temporary balloon occlusion to achieve proximal flow arrest in the parent vessel while embolizing the target vessel with a liquid embolic agent. Methods: A total of three vessel sacrifices (two vertebral, one carotid) were performed in three patients. Balloons were employed to achieve proximal flow arrest to allow an Onyx (Covidien) cast to accumulate in the target vessel following the deposition of coils. Results: Complete occlusion of the target vessel was achieved in all cases with no complications. Two balloons were employed, the Ascent (Covidien) and Scepter C (MicroVention). Between two and four coils and 0.3 to 0.7 cc of Onyx were employed resulting in significant cost, procedure and fluoroscopy time savings. Conclusion: Vessel sacrifice using commercially available non-adhesive liquid embolic agents is feasible with balloon assistance, allowing for reduced radiation and material costs. Coils may be beneficial in providing an anchor point for liquid embolic deposition, as well as reducing the volume of liquid embolysate required to achieve vessel occlusion. Competing interests: T Bhalla: None. A Spiotta: 1; C; Integra, Hemedex. F Hui: None.